Characteristics of Rainfall Deficit Anomalies During the Main Rice Planting Season in Indramayu Regency Based on the Standardized Precipitation Index (SPI) 2014–2024 - Marthin Abednego Gultom; Rafael Buwana; Chrisostommi Wirayudha Tuhumena (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study evaluates rainfall deficit anomalies during the main rice planting season to detect hidden meteorological droughts. It analyzes satellite-derived precipitation variables using the 1-month Standardized Precipitation Index (SPI-1). The observation timeline spans 2014 to 2024 across Indramayu Regency, utilizing CHIRPS spatial data. The results revealed that extreme drought anomalies surprisingly occurred during the peak wet seasons, specifically in December 2023 (SPI -2.48) and February 2024 (SPI -1.81). These anomalous wet-season precipitation failures severely disrupted the critical early vegetative phases of rice. The findings imply an urgent need for agricultural stakeholders to transition from static to dynamic planting calendars integrated with probability-based climate prediction models to mitigate mass crop failures.